The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.jhh.1002318
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional arterial properties in patients with obstructive sleep apnoea syndrome and cardiovascular comorbidities

Abstract: The increased severity of obstructive sleep apnoea syndrome (OSAS) is associated with a parallel increase in the incidence of cardiovascular events. Whether the increased severity of OSAS is in fact associated with impaired arterial properties has never been thoroughly studied. In patients with OSAS who carry a high burden of cardiovascular risk factors, we investigated whether the severity of OSAS is associated with deterioration in the arterial properties, independent of classical cardiovascular risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
(53 reference statements)
1
21
1
4
Order By: Relevance
“…48 More specifically, the study by Protogerou et al 48 did not find a direct association between OSA severity categories (moderate, severe and very severe) and arterial stiffness. However, they did find RDI to predict cfPWV significantly, the gold standard of arterial stiffness measurements.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…48 More specifically, the study by Protogerou et al 48 did not find a direct association between OSA severity categories (moderate, severe and very severe) and arterial stiffness. However, they did find RDI to predict cfPWV significantly, the gold standard of arterial stiffness measurements.…”
Section: Discussionmentioning
confidence: 93%
“…They found cfPWV to be significantly higher in patients with severe OSA as compared to both mild to moderate OSA and normal controls. Protogerou et al 48 determined cfPWV, augmentation index (AIx) and central blood pressure in mild, moderate and severe OSA patients. They found that these arterial stiffness parameters did not increase with the severity of OSA after adjustment for age, gender, body mass index, heart rate, mean blood pressure, smoking and diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The epidemiology, 8 genetic associations 9 and prognostic implications 10 of PWV (and arterial stiffness) have also been reported as has the relationship to haemodynamics, 11 cardiac structure and function. 12,13 Thus, it is increasingly important to have accurate and reproducible methods to assess PWV.…”
mentioning
confidence: 99%